2008
DOI: 10.1118/1.2889778
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a computationally efficient least‐squares algorithm for highly under‐determined three‐dimensional diffuse optical tomography problems

Abstract: Three-dimensional ͑3D͒ diffuse optical tomography is known to be a nonlinear, ill-posed and sometimes under-determined problem, where regularization is added to the minimization to allow convergence to a unique solution. In this work, a generalized least-squares ͑GLS͒ minimization method was implemented, which employs weight matrices for both data-model misfit and optical properties to include their variances and covariances, using a computationally efficient scheme. This allows inversion of a matrix that is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…The Woodbury formula can be used to find the matrix inverse to reduce calculation time because in an underdetermined problem, as is often the case in DOI, the Jacobian matrix has more columns than rows [34]. …”
Section: Mathematical Formulationmentioning
confidence: 99%
“…The Woodbury formula can be used to find the matrix inverse to reduce calculation time because in an underdetermined problem, as is often the case in DOI, the Jacobian matrix has more columns than rows [34]. …”
Section: Mathematical Formulationmentioning
confidence: 99%
“…In 3-D, Dehghani et al [20] used exact knowledge of boundaries and assumption of homogeneous piece-wise regions in a cylindrical shape in 3–D and showed nearly 100% recovery in experiments. Further work by Yalavarthy et al incorporated structural information in a generalized framework for optical imaging [21,22]. Azar et al [23] have demonstrated co-registration of non-concurrent NIR and MRI images and segmentation of MR images to enable priors to be applied in 3-D and have applied this to phantom models and three clinical cases.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this goal, the optimization equation is solved to recover the optical properties of the tissue. The procedure is usually based on a least-squares equation (linear or nonlinear) expressing the difference between the measured data and the expected measurements obtained from forward problem solution [55,56] . This last step has a number of challenges.…”
Section: Hardware and Image Reconstructionmentioning
confidence: 99%
“…These terms are added to the least-squares equation restricting the solution and enhancing the image. Basic Tikhonov zero-order regularization [58] and more complex functions such as truncated singular value decomposition have been implemented to improve the image quality [53,56,59] . The search for the appropriate regularization is in progress in the field of image reconstruction.…”
Section: Hardware and Image Reconstructionmentioning
confidence: 99%